2018
DOI: 10.1080/15384101.2018.1482138
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of LIMK1/2 in actin assembly during mouse embryo development

Abstract: LIMKs (LIMK1 and LIMK2) are serine/threonine protein kinases that involve in various cellular activities such as cell migration, morphogenesis and cytokinesis. However, its roles during mammalian early embryo development are still unclear. In the present study, we disrupted LIMK1/2 activity to explore the functions of LIMK1/2 during mouse early embryo development. We found that p-LIMK1/2 mainly located at the cortex of each blastomeres from 2-cell to 8-cell stage, and p-LIMK1/2 also expressed at morula and bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Inactivation of LIMKs through silencing with dsRNA or the use of the LIMK inhibitor LIMKi3, which shows a good selectivity within the kinome (see the recent review by Chatterjjee and collaborators [30]), induced the disruption of adherent junctions, resulting in the early termination of development before the blastocyst stage [31]. A similar observation was made in an analysis of early mouse embryogenesis: the use of the LIMKi3 inhibitor caused the failure of early blastomere cleavage, compaction and blastocyst formation [32]. These results point to a crucial role of LIMKs during the early stages of development.…”
Section: Expression Of Limks During Developmentmentioning
confidence: 67%
“…Inactivation of LIMKs through silencing with dsRNA or the use of the LIMK inhibitor LIMKi3, which shows a good selectivity within the kinome (see the recent review by Chatterjjee and collaborators [30]), induced the disruption of adherent junctions, resulting in the early termination of development before the blastocyst stage [31]. A similar observation was made in an analysis of early mouse embryogenesis: the use of the LIMKi3 inhibitor caused the failure of early blastomere cleavage, compaction and blastocyst formation [32]. These results point to a crucial role of LIMKs during the early stages of development.…”
Section: Expression Of Limks During Developmentmentioning
confidence: 67%
“…The weight of the testes in LIMK2−/− mice was significantly reduced to approximately 80% compared to that of control mice (Takahashi et al, 2002). In addition, the inhibition of LIMK1/2 activity in mouse causes the failure of embryo cleavage and blastocyst formation (Duan et al, 2018). Fanconi anemia (FANCA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development.…”
Section: Discussionmentioning
confidence: 99%
“…LIMK acts downstream of Rho-GTPase and is mainly distributed in actin synthesis sites, involved in the regulation of cytoskeletal dynamics and cell proliferation during embryo development [ 14 ]. Previous studies showed that another Rho-GTPase effector, ROCK, which is located in the nucleus and cytoplasm [ 9 ], is required for blastocyst cavity formation and normal ICM differentiation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…LIMK1/2 regulate spindle organization and F-actin levels by phosphorylation of cofilin during mammalian oocyte maturation [ 13 ]. Inhibition of LIMK1/2 impairs cell division and disrupts actin dynamics during mouse early embryo development [ 14 ]. Although the mouse is a more beneficial experimental animal for developmental biology, different processes during early embryo development such as the timing of zygotic genome activation, the period between 1-cell to blastocyst formation, and gene expression patterns are more suitable for study in pigs.…”
Section: Introductionmentioning
confidence: 99%